A kind of carbon-coated aluminum foil and preparation method thereof
By using carbon-coated aluminum foil grafted carbon nanotubes and polymerizable monomers and other materials in the production process of carbon-coated aluminum foil, combined with ultraviolet curing film formation technology, the problems of high energy consumption and environmental pollution of existing carbon-coated aluminum foils are solved. , achieving a more efficient and environmentally friendly production process.
Patent Information
- Application Number
- CN202310360153.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-04-06
AI Technical Summary
In the production process of existing carbon-coated aluminum foils, there are problems such as high energy consumption drying process and carbon coating layers that are prone to cross-grain and environmental pollution.
Carbon-coated aluminum foil is prepared by using a photoinitiator to graft onto the carboxylated carbon nanotubes and added to the slurry of polymerizable monomer, conductive agent, prepolymer and polymerization inhibitor. , reducing solvent use and drying process.
It improves the adhesion and conductivity of the carbon coated layer, reduces equipment energy consumption and production costs, and avoids environmental pollution.
Smart Images

Figure CN116741918B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium batteries, and in particular relates to a carbon-coated aluminum foil and a preparation method thereof. Background Art
[0002] In recent years, due to the increasing demand for energy and the vigorous development of new energy, the lithium battery industry has developed rapidly. In particular, benefiting from the rising demand for new energy vehicles, the proportion of lithium-ion batteries used in my country will continue to increase. Compared with traditional batteries, lithium-ion batteries have large capacity, long life, and good cycle times, and are widely used in the automotive and consumer electronics fields. In addition, lithium-ion batteries can also be used in energy storage products. New energy storage technology will change the existing energy structure and electricity production and consumption methods. With the commercialization of lithium batteries, power lithium-ion batteries will participate in future social production as a component of the new energy industry. Therefore, how to improve the energy density of lithium batteries has become the key to the research and development of power lithium batteries, and the improvement of battery materials provides technical support for improving the performance of lithium batteries.
[0003] In the production process of lithium batteries, since the particles of the positive electrode slurry are relatively large, they are in surface and point contact with the aluminum foil. If the aluminum foil (current collector) directly contacts the positive electrode active material, the contact resistance between the aluminum foil and the positive electrode active material is relatively large. In order to reduce the contact resistance, carbon-coated aluminum foil is currently used. Carbon-coated aluminum foil is a layer of conductive carbon layer coated on the aluminum foil, that is, a layer of conductive carbon layer is added between the aluminum foil and the positive electrode active material, which can significantly reduce the contact resistance.
[0004] However, the current carbon-coated aluminum foil has the following main disadvantages:
[0005] (1) Conventional carbon-coated aluminum foil requires two processes: slurry coating and high-temperature drying. The drying process is carried out at a relatively high temperature (200-600°C), and the required drying equipment consumes a lot of energy, which is not conducive to reducing production costs.
[0006] (2) After rolling, the aluminum foil has transverse lines. When preparing the carbon coating slurry, in order to disperse it evenly, a large amount of solvent is used, and the solvent content is about 50-80%. When the slurry is dried, as the solvent in the slurry evaporates, the volume of the carbon coating layer shrinks in the transverse direction, so it is easy to cause transverse lines in the carbon coating layer, which leads to uneven current in the current collector.
[0007] (3) Most of the carbon-coated slurries that are dried to form films contain volatile organic solvents. The volatilization of organic solvents during drying is not conducive to environmental protection. During the drying process, the volatilization of solvents can easily cause orange peel and shrinkage phenomena. Summary of the invention
[0008] The present invention aims to solve one of the technical problems existing in the prior art to at least a certain extent. To this end, the present invention provides a carbon-coated aluminum foil and a preparation method thereof. The carbon-coated aluminum foil obtained by the preparation method of the present invention has strong adhesion between the carbon coating layer and the aluminum foil, which can reduce the contact resistance. Since the polymer content in the carbon coating layer is reduced, the solvent resistance is improved. At the same time, the preparation method can also improve the lateral unevenness of the carbon coating layer caused by the uneven surface of the substrate.
[0009] In one aspect, the present invention provides a method for preparing a carbon-coated aluminum foil, the method comprising the following steps:
[0010] (1) Pretreatment: Grafting a photoinitiator onto the carboxylated carbon nanotubes to obtain photoinitiator-grafted carbon nanotubes;
[0011] (2) preparing a slurry: adding a polymerizable monomer, a prepolymer, a conductive agent and a polymerization inhibitor, and performing a first mixing; adding carbon nanotubes grafted with a photoinitiator, and performing a second mixing to obtain a slurry;
[0012] (3) Applying slurry: applying the prepared slurry on aluminum foil;
[0013] (4) Curing: Place the aluminum foil coated with the slurry under ultraviolet light to cure into a film.
[0014] According to some embodiments of the present invention, the method for preparing the carbon-coated aluminum foil provided by the present invention may further include the following subsidiary technical features:
[0015] (1) Pre-treatment:
[0016] In some embodiments, the pretreatment in step (1) includes: firstly subjecting the carboxylated carbon nanotubes to an acylation reaction with thionyl chloride in solvent A to obtain chlorinated carbon nanotubes, and then subjecting the chlorinated carbon nanotubes to a photoinitiator grafting reaction with a photoinitiator in the presence of a base in solvent B to obtain photoinitiator grafted carbon nanotubes.
[0017] Furthermore, in step (1), the photoinitiator molecule contains a group such as a hydroxyl group or an amino group that can react with an acyl chloride.
[0018] Furthermore, in step (1), the photoinitiator is selected from one or more of benzoin derivatives, benzyl ketal compounds, α,α-dialkoxyacetophenone compounds, α-hydroxyalkyl phenone compounds, α-aminoalkyl phenone compounds or acylphosphine oxide compounds.
[0019] Specifically, in step (1), the photoinitiator is one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959, CAS No.: 106797-53-9), 1,1'-(oxybis(4,1-phenylene))bis(2-hydroxy-2-methyl-1-propanone) (photoinitiator 160, CAS No.: 71868-15-0), bis(2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane) (photoinitiator 150, CAS: 163702-01-0) or 1,1'-(methylenebis-4,1-phenylene)bis(2-hydroxy-2-methyl-1-propanone) (photoinitiator 127, CAS No.: 474510-57-1).
[0020] Furthermore, in step (1), the carboxylated carbon nanotubes are selected from carbon nanotubes having an outer diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of more than 300 m 2 / g of single-walled or multi-walled carbon nanotubes.
[0021] In the present invention, the outer diameter, length and specific surface area of the carboxylated carbon nanotubes can be adjusted according to experimental requirements, and other parameters and other carboxylated carbon nanotubes that can achieve the technical effects described in the present invention can also be used in the present invention.
[0022] Furthermore, in step (1), the content of functionalized carboxyl groups in the carboxylated carbon nanotubes is greater than 2 wt%.
[0023] Specifically, in step (1), the content of functionalized carboxyl groups in the carboxylated carbon nanotubes is 2.73 wt %.
[0024] In step (1), the more functionalized carboxyl groups in the carboxylated carbon nanotubes used, the more photoinitiators can be connected. When the functionalized carboxyl groups are less than 2 wt%, the comb-like structure formed during polymerization is reduced and the adhesion is reduced.
[0025] According to some embodiments of the present invention, in step (1), the conditions of the acylation reaction are as follows:
[0026] The mass ratio of the carboxylated carbon nanotubes to thionyl chloride is 1:(0.3-3).
[0027] Specifically, the mass ratio of the carboxylated carbon nanotubes to thionyl chloride is 1:(0.3-1).
[0028] More specifically, the mass ratio of the carboxylated carbon nanotubes to thionyl chloride is 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.9 or any value within the range of 1:(0.3-1).
[0029] The solvent A is an organic solvent.
[0030] Specifically, the solvent A is selected from one or more of chloroform, dichloromethane, ethyl acetate, acetone, acetonitrile or tetrahydrofuran.
[0031] More specifically, the solvent A is chloroform.
[0032] Specifically, the reaction temperature is 25-50° C., and the reaction time is 1-10 h.
[0033] More specifically, the reaction temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or any value within the range of 25 to 50°C.
[0034] More specifically, the reaction time is 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the range of 1-10 h.
[0035] The acylation reaction was carried out under nitrogen protection.
[0036] According to some embodiments of the present invention, in step (1), the conditions of the photoinitiator grafting reaction are as follows:
[0037] The mass ratio of the chlorinated carbon nanotubes to the photoinitiator is 1:(0.3-5).
[0038] Specifically, the mass ratio of the chlorinated carbon nanotubes to the photoinitiator is 1:(0.3-1).
[0039] More specifically, the mass ratio of the chlorinated carbon nanotubes to the photoinitiator is 1:0.3, 1:0.5, 1:0.7, 1:0.8 or any value within the range of 1:(0.3-1).
[0040] The mass ratio of the chlorinated carbon nanotubes to the base is 1:(0.3-10).
[0041] Specifically, the mass ratio of the chlorinated carbon nanotubes to the base is 1:(0.3-3).
[0042] More specifically, the mass ratio of the chlorinated carbon nanotubes to the base is 1:0.3, 1:0.5, 1:0.6, 1:0.7, 1:2, 1:3 or any value within the range of 1:(0.3-3).
[0043] The solvent B is an organic solvent.
[0044] Specifically, the solvent B is selected from one or more of chloroform, dichloromethane, ethyl acetate, acetone, acetonitrile or tetrahydrofuran.
[0045] More specifically, the solvent B is chloroform.
[0046] Since the chemical bonds in the photoinitiator are relatively weak, the photoinitiator molecules are not stable and are easily decomposed when the temperature is too high, so the reaction temperature should not be too high.
[0047] Specifically, the reaction temperature is 25-50° C., and the reaction time is 1-10 h.
[0048] More specifically, the reaction temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or any value within the range of 25 to 50°C.
[0049] More specifically, the reaction time is 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the range of 1-10 h.
[0050] The base may be an organic base or an inorganic base.
[0051] Specifically, the base is one or more of triethylamine, diethylamine, pyridine, potassium carbonate, sodium carbonate, sodium bicarbonate or potassium bicarbonate. More specifically, the base is triethylamine.
[0052] The photoinitiator grafting reaction is carried out under light protection and nitrogen protection.
[0053] In some embodiments, the step (1) is specifically as follows: adding carboxylated carbon nanotubes to solvent A, stirring and dispersing, adding thionyl chloride dropwise under nitrogen protection, stirring at 25-50° C. for 1-10 hours, and after the reaction is complete, filtering the reaction mixture to obtain a black filter cake, and repeatedly washing the filter cake with solvent A to obtain chlorinated carbon nanotubes.
[0054] The chlorinated carbon nanotubes are added to solvent B, stirred and dispersed, a photoinitiator is added under the protection of nitrogen and light, a certain amount of alkali is added, and the mixture is stirred at 25-50°C for 1-10 hours. After the reaction is complete, the reaction mixture is filtered to obtain a black filter cake. The filter cake is repeatedly washed with solvent B, and after vacuum drying at 10-30°C in the dark, carbon nanotubes grafted with the photoinitiator are obtained.
[0055] Furthermore, in step (1), the temperature of the light-proof vacuum drying is specifically 10°C, 15°C, 20°C, 25°C, 30°C or any value within the range of 10 to 30°C.
[0056] In other embodiments, the step (1) is specifically as follows: adding the carboxylated carbon nanotubes to solvent A, stirring and dispersing, adding thionyl chloride dropwise under nitrogen protection, stirring at 25-50° C. for 1-10 hours, and after the reaction is complete, filtering the reaction mixture to obtain a black filter cake, and repeatedly washing the filter cake with solvent A to obtain chlorinated carbon nanotubes.
[0057] The chlorinated carbon nanotubes are added to solvent B, stirred and dispersed, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) is added under the protection of nitrogen and light, a certain amount of triethylamine is added dropwise, and the mixture is stirred at 25-50°C for 1-10h. After the reaction is complete, the reaction mixture is filtered to obtain a black filter cake, which is repeatedly washed with solvent B, and dried in a vacuum at 10-30°C in the dark to obtain carbon nanotubes grafted with a photoinitiator.
[0058] In step (1), the solvent A and the solvent B may be the same or different.
[0059] (2) Preparation of slurry
[0060] Furthermore, in step (2), the polymerizable monomer is one or more of acrylic monomers, acrylate monomers, styrene monomers or allyl monomers.
[0061] Furthermore, in step (2), the acrylic monomer is selected from one or a combination of acrylic acid or methacrylic acid.
[0062] Furthermore, in step (2), the acrylic acid ester monomer is selected from one or more of methyl acrylate, ethyl acrylate, butyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, 4-hydroxybutyl acrylate, 2-isocyanate ethyl acrylate, vinyl methacrylate, ethyl 2-cyanoacrylate, glycidyl methacrylate, phenyl acrylate, and phenyl methacrylate.
[0063] Furthermore, in step (2), the styrene monomer is selected from one or more of styrene, 2-methylstyrene, vinyltoluene, 4-isopropenyltoluene, 4-tert-butylstyrene, 3-methylstyrene, and 4-methoxystyrene.
[0064] Furthermore, in step (2), the allyl monomer is selected from one or more of allyl methyl sulfide, allyl methacrylate, allyl acetate, allyl acetoacetate, allyl butyl ether, allyl methyl carbonate, and allyl phenyl ether.
[0065] In the present invention, the polymerizable monomer can be adjusted according to experimental requirements and is not specific. The technical effects of the present invention can be achieved by using the polymerizable monomers alone or in combination.
[0066] Furthermore, in step (2), the prepolymer is selected from one or more of polyether acrylate, epoxy acrylate resin, and polyurethane acrylate.
[0067] Specifically, in step (2), the prepolymer is polyurethane acrylate.
[0068] Preferably, the polyurethane acrylate has a functionality of 2-6, a viscosity of 500-20000 cps, and a number average molecular weight of 200-700.
[0069] More preferably, polyurethane acrylates of different functionalities, viscosities and number average molecular weights may be used in combination.
[0070] In the present invention, the functionality, viscosity and number average molecular weight of the polyurethane acrylate can be adjusted according to experimental requirements and are not specific. Other parameters and other types of polyurethane acrylate can also achieve the technical effects of the present invention.
[0071] Furthermore, in step (2), the conductive agent is selected from one or more of conductive carbon black SP, conductive graphite KS-6, graphene, carbon fiber or carbon nanotube.
[0072] In some embodiments, the conductive agent is selected from two of conductive carbon black SP, conductive graphite KS-6, graphene, carbon fiber or carbon nanotube.
[0073] In the present invention, the conductive agent can be adjusted according to experimental requirements, and can be used alone or in combination. When the conductive agents are used in combination, electrons can be transmitted along the sheet and can move between different sheets, thereby increasing conductivity.
[0074] When the conductive agents are used in combination, preferably, the conductive agent is a combination of conductive carbon black SP and conductive graphite KS-6.
[0075] Furthermore, the mass ratio of the conductive carbon black SP to the conductive graphite KS-6 is (1-100):(1-100).
[0076] Specifically, the mass ratio of the conductive carbon black SP to the conductive graphite KS-6 is 100:1, 50:1, 1.5:1, 1:1, 1:1.5, 1:50, 1:100 or any value in the range of (1-100):(1-100).
[0077] Furthermore, in step (2), the inhibitor is selected from one or more of p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butylhydroquinone, hydroquinone, methylhydroquinone, p-benzoquinone, vinyl acetate, aniline, diphenylamine, benzidine, and p-phenylenediamine.
[0078] Furthermore, in step (2), the mass ratio of the polymerizable monomer, the prepolymer, the conductive agent and the polymerization inhibitor is 1:(0.01-0.20):(0.4-2.50):(0.01-0.35).
[0079] Furthermore, in step (2), the mass ratio of the polymerizable monomer, the prepolymer, the conductive agent and the polymerization inhibitor is 1:(0.02-0.1):(0.9-2):(0.01-0.1).
[0080] Specifically, in step (2), the mass ratio of the polymerizable monomer, prepolymer, conductive agent and inhibitor is any value within the range of 1:0.02:1:0.01, 1:0.04:1:0.01, 1:0.04:1.02:0.01, 1:0.1:2:0.1 or 1:(0.02-0.1):(0.9-2):(0.01-0.1).
[0081] Furthermore, in step (2), the mass ratio of the polymerizable monomer to the carbon nanotubes grafted with the photoinitiator is (0.8-2):(0.01-0.5).
[0082] Furthermore, in step (2), the mass ratio of the polymerizable monomer to the carbon nanotubes grafted with the photoinitiator is (0.8-1):(0.01-0.1).
[0083] Specifically, in step (2), the mass ratio of the polymerizable monomer to the carbon nanotubes grafted with the photoinitiator is 1:0.01, 1:0.02, 1:0.04, 1:0.05, 1:0.1 or any value in the range of (0.8-1):(0.01-0.1).
[0084] Furthermore, if the amount of the photoinitiator-grafted carbon nanotubes is too little, the polymerization of the polymerizable monomer will be incomplete, and it will not be easy to dry when forming a film; if the amount of the photoinitiator-grafted carbon nanotubes is too much, the viscosity of the slurry will be too high, the leveling property will be poor, and the coating will be uneven when applied.
[0085] Furthermore, in step (2), other auxiliary agents are also included, and the other auxiliary agents can further optimize the film-forming effect after coating.
[0086] Furthermore, the mass ratio of the polymerizable monomer to other auxiliary agents is 1:(0.01-0.3).
[0087] Furthermore, the mass ratio of the polymerizable monomer to other auxiliary agents is 1:(0.02-0.1).
[0088] Specifically, the mass ratio of the polymerizable monomer to other auxiliary agents is 1:0.02, 1:0.04, 1:0.06, 1:0.1 or any value within the range of 1:(0.02-0.1).
[0089] Furthermore, in step (2), the other auxiliary agent is selected from one or more of a wetting and dispersing agent, a leveling agent, a silane coupling agent, a thickener or a defoaming agent, wherein the other auxiliary agent cannot react with a polymerizable monomer or a photoinitiator.
[0090] Further, in step (2), the wetting and dispersing agent is one or more of BYK-ET3000, BYK-ET3001, BYK-ET3002, BYK-ET3003, BYK-ET3004, BYK-ET 3031, BYK-ET 3032, BYK-ET 3033, BYK-ET 3034, Electro-Rite AL003 or Electro-Rite BD040.
[0091] Furthermore, in step (2), the thickener is one or more of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, chitin or chitosan.
[0092] Further, in step (2), the leveling agent is one or more of BYKETOL-WA, BYK-UV 3575, BYK-UV 3576, BYK-UV 3535 or BYK-UV 3570.
[0093] Furthermore, in step (2), the silane coupling agent is one or more of isobutyltriethoxysilane, vinyltriethoxysilane (A151), vinyltrimethoxysilane (A171) or vinyltri(β-methoxyethoxy)silane (A172).
[0094] Furthermore, in step (2), the defoaming agent is one or more of BYK-1707, BYK-1709, BYK-1758, BYK-1759 or BYK-1791.
[0095] In some embodiments, the other adjuvants include wetting and dispersing agents and thickening agents.
[0096] Furthermore, in step (2), the mass ratio of the wetting and dispersing agent to the thickener is (1-10):(1-10).
[0097] Furthermore, in step (2), the mass ratio of the wetting and dispersing agent to the thickening agent is (1-5):(1-5).
[0098] Specifically, in step (2), the mass ratio of the wetting and dispersing agent to the thickener is 1:1, 1:3, 1:5, 2:1, 3:1, 5:1 or any value within the range of (1-5):(1-5).
[0099] Furthermore, in step (2), the first mixing includes: first mechanical stirring, then sand grinding; the second mixing includes: first mechanical stirring, then sand grinding.
[0100] Furthermore, in step (2), in the first mixing and the second mixing, the temperature of the mechanical stirring is room temperature, and the stirring time is not particularly limited. From the perspective of improving efficiency, it can be controlled within 1-2 hours.
[0101] Specifically, in the first mixing and the second mixing, the time of the mechanical stirring is independently 1 h, 1.5 h, 2 h or any value within the range of 1-2 h.
[0102] Furthermore, in step (2), during the first mixing and the second mixing, the temperature during the sand grinding is controlled within the range of -10 to 10°C.
[0103] Specifically, in step (2), in the first mixing and the second mixing, the sand grinding temperature is independently -10°C, -5°C, 0°C, 5°C, 10°C or any value within the range of -10 to 10°C.
[0104] In step (2), the sand grinding temperature should be controlled within the range of -10 to 10°C, because the polymerizable monomer in the slurry formulation contains a double bond structure, and when the temperature is too high, the double bond will initiate a polymerization reaction.
[0105] Furthermore, in step (2), in the first mixing and the second mixing, the sand grinding time is independently 0.1-4h.
[0106] Specifically, the sanding time is independently 0.1h, 0.5h, 1h, 2h, 3h, 4h or any value in the range of 0.1-4h.
[0107] Furthermore, in order to improve the storage performance of the slurry, an inhibitor may be added to the slurry. When the slurry is stored in a container, a certain amount of air should be left on the top of the container to inhibit polymerization.
[0108] During the preparation process of the slurry of the present invention, no solvent in any form is added, and the slurry is environmentally friendly.
[0109] Furthermore, in step (2), the second mixing is performed under light-proof conditions.
[0110] (3) Coating slurry
[0111] Furthermore, before applying the slurry in step (3), the aluminum foil is pretreated to increase its surface roughness.
[0112] The pretreatment method includes, but is not limited to: using ultrasonic equipment to clean the surface of the aluminum foil, then corroding the surface of the aluminum foil with acid or etching the surface of the aluminum foil with plasma equipment.
[0113] Furthermore, in the pretreatment step, the acid is selected from one or more of hydrochloric acid, nitric acid, phosphoric acid or sulfuric acid.
[0114] Furthermore, in the pretreatment step, the pH value of the acid is 5-7.
[0115] Specifically, in the pretreatment step, the pH value of the acid is 5, 6, 7 or any value in the range of 5-7.
[0116] Furthermore, in the pretreatment step, the thickness of the aluminum foil corrosion does not exceed 5 μm.
[0117] Furthermore, in step (3), the slurry is coated under light-proof or yellow light conditions, and the coating method is wire rod coating, doctor blade coating or micro-concave roller coating.
[0118] Furthermore, in step (3), the slurry is coated under light-proof or yellow light conditions, and the coating method is wire rod coating.
[0119] The yellow light is also called the anti-ultraviolet yellow safety light, which adopts a unique coating to eliminate 500nm ultraviolet rays. It almost does not emit blue-violet light below 500nm, and only contains pure yellow spectrum.
[0120] Furthermore, in step (3), the wire rod has a specification of 5-10 μm.
[0121] Specifically, in step (3), the wire rod specification is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value within the range of 5-10 μm.
[0122] Furthermore, in step (3), when the slurry is applied, the wet film thickness is between 5 and 10 μm.
[0123] Specifically, in step (3), when the slurry is coated, the wet film thickness is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value within the range of 5-10 μm.
[0124] When coating the slurry, the wet film thickness should be between 5-10μm. Due to the weak penetration of UV light, if the coating is too thick, the UV light cannot penetrate into the deeper slurry, which will be detrimental to UV-induced curing and lead to incomplete curing, which will reduce the adhesion of the coating.
[0125] (4) Curing
[0126] Furthermore, the step (4) is carried out in a vacuum or inert atmosphere to avoid oxygen inhibition.
[0127] Furthermore, in step (4), the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.
[0128] Furthermore, in step (4), the UV curing time is 30-100s.
[0129] Specifically, in step (4), the UV curing time is 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s or any value within the range of 30-100s.
[0130] Furthermore, in step (4), the wavelength range of the ultraviolet light source is 300-380nm, and the ultraviolet light energy is 100-1500mJ / cm 2 .
[0131] In the present invention, taking the polymerizable monomer as an acrylate monomer as an example, the reaction mechanism is shown in Formula I, the carboxyl group on the carboxylated carbon nanotube is chlorinated by thionyl chloride to obtain chlorinated carbon nanotubes; the hydroxyl group or amino group of the photoinitiator and the acyl chloride on the carbon nanotube react to graft the photoinitiator onto the carbon nanotube to obtain a "carbon nanotube-photoinitiator" compound (photoinitiator-grafted carbon nanotube); then, the "carbon nanotube-photoinitiator" compound and polymerizable monomers, prepolymers, conductive agents, inhibitors, other additives and other components are configured to obtain a slurry, after the slurry is coated on aluminum foil, the coating is irradiated with ultraviolet light, the "carbon nanotube-photoinitiator" compound absorbs ultraviolet light, a Norrish reaction occurs, and it is decomposed into free radical initiating groups, which initiate the polymerization and curing of the polymerizable monomers into a film.
[0132]
[0133] In order to avoid coating defects caused by heating during drying film formation, technicians in this field improved the drying film formation method to the photocuring film formation method. The advantage of photocuring film formation is that it can be carried out at room temperature. The existing photopolymerization process is to polymerize the polymerizable monomers in the slurry into linear polymers, and the polymer film formation plays the role of bonding aluminum foil. However, due to the insufficient winding points of the linear polymer, the adhesion of the conductive coating is poor. In order to enhance the adhesion of the coating, the present invention first grafts a photoinitiator onto the tube wall of the carboxylated carbon nanotube to obtain a modified photoinitiator-grafted carbon nanotube, then adds the photoinitiator-grafted carbon nanotube into a slurry prepared by mixing components such as a polymerizable monomer, a conductive agent, a prepolymer, a conductive agent, an inhibitor and other additives, and after coating on an aluminum foil, a Norrish reaction occurs under ultraviolet light, the photoinitiator is decomposed to generate free radical fragments, the free radical fragments are connected to the carbon nanotubes to form "carbon nanotube-free radical fragments", after initiating polymerization, the polymerizable monomer is grafted onto the carbon nanotubes through the free radical fragments grafted on the carbon nanotubes to form a comb-like structure, forming a "carbon nanotube-free radical fragment-polymerized monomer" brush-type structure, which is conducive to the entanglement of the polymer, is conducive to enhancing the adhesion of the carbon coating layer, and improves the conductivity of the carbon-coated aluminum foil, and can also reduce the amount of polymer used and improve solvent resistance.
[0134] In the present invention, taking the polymerizable monomer as an acrylic ester monomer as an example, the comb-like structure formed is as shown in Formula II:
[0135]
[0136] The slurry of the present invention does not use solvents, thus avoiding horizontal lines and environmental pollution caused by solvent volatilization. The photoinitiator on the surface of the wet film decomposes to obtain free radicals, and the chain growth of the polymerization reaction is conducted from the surface of the wet film to the inside of the wet film. The shrinkage of the volume of the coating layer caused by polymerization is a longitudinal shrinkage perpendicular to the surface of the aluminum foil. The rolling process of the aluminum foil is prone to produce horizontal lines parallel to the surface of the aluminum foil, thereby making the surface of the substrate uneven. The rolling horizontal lines are prone to cause horizontal lines in the carbon coating layer. Since the volume shrinkage caused by photocuring film formation is perpendicular to the plane of the aluminum foil, the lateral unevenness of the carbon coating layer caused by the uneven surface of the substrate can be reduced, and the generation of horizontal lines can be reduced. After the aluminum foil is coated with the slurry, it is cured by ultraviolet light polymerization at room temperature to avoid heating so that the carbon coating layer causes orange peel phenomenon and shrinkage cavity phenomenon due to thermal expansion and contraction. In addition, the energy consumption required by the photocuring equipment is less than that of the drying equipment, which is conducive to cost saving.
[0137] In another aspect, the present invention provides a carbon-coated aluminum foil prepared by the method of the present invention.
[0138] In another aspect, the present invention provides a current collector comprising the carbon-coated aluminum foil of the present invention.
[0139] The beneficial effects of the present invention are:
[0140] (1) A photoinitiator is first grafted onto carboxylated carbon nanotubes, and then a polymerizable monomer is grafted onto the wall of the carbon nanotubes grafted with the photoinitiator through photoinitiator fragments to obtain a comb-like structure, which is conducive to the entanglement of the polymer. The carbon nanotubes and the polymer are in a cross-linked state, which is conducive to enhancing the adhesion of the carbon coating layer; the amount of polymer used can be reduced, the resistance of the carbon-coated aluminum foil can be reduced, and the solvent resistance can be improved.
[0141] (2) When ultraviolet light irradiates the slurry, the photoinitiator on the surface of the wet film decomposes to obtain free radicals, and the chain growth of the polymerization reaction is transmitted from the surface of the wet film to the inside of the wet film. The polymerization causes the volume of the coating layer to shrink, and it is a vertical shrinkage in the longitudinal direction, reducing the lateral unevenness of the carbon coating layer caused by the uneven surface of the substrate.
[0142] (3) UV light curing is used to form a film, avoiding the heating and drying process, reducing equipment energy consumption and production costs.
[0143] (4) Do not use volatile organic solvents to avoid orange peel and shrinkage phenomena during film formation. No volatile gas is generated during film formation, reducing environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0144] Figure 1 This is a surface image of the carbon-coated aluminum foil prepared in Example 1;
[0145] Figure 2 This is a surface image of the carbon-coated aluminum foil prepared in Comparative Example 2.
[0146] Specific implementation scheme
[0147] The following description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0148] The method for preparing the carbon-coated aluminum foil of the present invention specifically comprises the following steps:
[0149] (1) Pretreatment: Grafting a photoinitiator onto the carboxylated carbon nanotubes to obtain photoinitiator-grafted carbon nanotubes;
[0150] Add carboxylated carbon nanotubes to solvent A, stir and disperse, add thionyl chloride dropwise under nitrogen protection, stir at 25-50°C for 1-10h, after the reaction is complete, filter the reaction mixture to obtain a black filter cake, wash the filter cake repeatedly with solvent A to obtain chlorinated carbon nanotubes.
[0151] The chlorinated carbon nanotubes are added to solvent B, stirred and dispersed, and a photoinitiator is added under the protection of nitrogen and light, and a certain amount of alkali is added, and stirred at 25-50°C for 1-10 hours. After the reaction is complete, the reaction mixture is filtered to obtain a black filter cake, and the filter cake is repeatedly washed with solvent B. After vacuum drying at 10-30°C in the dark, the carbon nanotubes grafted with the photoinitiator are obtained.
[0152] (2) Preparation of slurry
[0153] Add polymerizable monomers, prepolymers, conductive agents, polymerization inhibitors and other additives, first mechanically stir, then sand grind; under light-proof conditions, add carbon nanotubes grafted with photoinitiators, first mechanically stir, then sand grind to obtain slurry;
[0154] Preferably, the other auxiliary agents include wetting and dispersing agents and thickeners.
[0155] The mechanical stirring temperatures were both room temperature;
[0156] The time of the two mechanical stirrings is 1-2h independently;
[0157] The temperature was controlled within the range of -10 to 10°C during both sanding operations;
[0158] The sanding times for the two times are independently 0.1-4h.
[0159] (3) Coating slurry
[0160] Pre-treat the aluminum foil to increase the roughness of the aluminum foil surface: use ultrasonic equipment to clean the aluminum foil surface, and then use acid to corrode the aluminum foil surface. You can use hydrochloric acid, nitric acid, phosphoric acid or sulfuric acid solutions with a pH value of 5-7; or use plasma equipment to etch the aluminum foil surface. The thickness of the aluminum foil corrosion does not exceed 5μm.
[0161] The coating is carried out in a dark environment or under a yellow light condition, wherein the coating method is wire rod coating, blade coating or micro-concave roller coating;
[0162] The wet film thickness is between 5-10μm.
[0163] (4) UV curing film
[0164] Place the aluminum foil coated with the slurry in a vacuum or oxygen-free inert atmosphere. The inert atmosphere can be nitrogen or argon. Irradiate with ultraviolet light for 30-100s. The wavelength range of the ultraviolet light source is 300-380nm, and the ultraviolet light energy is 100-1500mJ / cm 2 .
[0165] The embodiments of the present invention will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if specific conditions are not specified, the conditions described in the specification, normal conditions or conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0166] Embodiment 1:
[0167] 10g of carboxylated single-walled carbon nanotubes (outer diameter 1-2nm, length 5-30μm, specific surface area greater than 300m 2 / g, carboxylation 2.73wt%) was dispersed in 200mL chloroform, 5g thionyl chloride was added dropwise under nitrogen protection, and the reaction was carried out at 50°C for 3h until no gas was released. The obtained reaction mixture was filtered to obtain a black filter cake, which was washed with chloroform to remove excess thionyl chloride to obtain chlorinated carbon nanotubes.
[0168] The chlorinated carbon nanotubes were dispersed in 200 mL of chloroform, and 5 g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) was added under light-proof and nitrogen protection conditions, and 5 g of triethylamine was added dropwise at 25°C. The reaction mixture was reacted for 3 hours, and the obtained reaction mixture was filtered to obtain a black filter cake. The filter cake was washed with chloroform to remove excess 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) and triethylamine. After vacuum drying at 25°C in the dark, 10.29 g of carbon nanotubes grafted with the photoinitiator were obtained.
[0169] Weigh respectively: 25g of butyl acrylate, 25g of hydroxyethyl acrylate, 2g of polyurethane acrylate prepolymer (functionality: 2-4), 1g of conductive carbon black SP, 50g of conductive graphite KS-6, 1g of carboxymethyl cellulose, 1g of BYK-ET3003 wetting and dispersing agent, and 0.5g of p-hydroxyanisole (inhibitor MEHQ), and first mechanically stir the materials at a stirring speed of 500 rev / min and stir at room temperature for 1h, then transfer them to a sand mill and wet-mill with zirconium beads having a diameter of 0.8mm, control the temperature at 10°C, and mill for 4h to obtain a pre-dispersed first mixed slurry; under light-proof conditions, add 1g of carbon nanotubes grafted with a photoinitiator, first mechanically stir at a stirring speed of 500 rev / min and stir at room temperature for 1h, then transfer them to a sand mill and wet-mill with zirconium beads having a diameter of 0.8mm, control the temperature at 10°C, and mill for 30 minutes to obtain a slurry for photocuring film formation.
[0170] An aluminum foil with a thickness of 15 μm is cleaned with an ultrasonic device, and then the surface of the aluminum foil is etched with a hydrochloric acid solution to increase the roughness of the aluminum foil. The pH value of the hydrochloric acid solution is between 5 and 7, and the thickness of the corrosion layer does not exceed 5 μm. The hydrochloric acid solution is washed off after the corrosion treatment.
[0171] Under light-proof conditions, the slurry was coated on aluminum foil with a 5 μm wire rod, and the wet film thickness was 5 μm. The aluminum foil coated with the wet film was placed in a nitrogen atmosphere and irradiated with ultraviolet light with a wavelength of 300-380 nm for 60 seconds to cure the film to obtain a carbon-coated aluminum foil.
[0172] Example 2
[0173] 10g of carboxylated single-walled carbon nanotubes (outer diameter 1-2nm, length 5-30μm, specific surface area greater than 300m 2 / g, carboxylation 2.73wt%) was dispersed in 200mL chloroform, 5g thionyl chloride was added dropwise under nitrogen protection, and the reaction was carried out at 50°C for 3h until no gas was released. The obtained reaction mixture was filtered to obtain a black filter cake, which was washed with chloroform to remove excess thionyl chloride to obtain chlorinated carbon nanotubes.
[0174] The chlorinated carbon nanotubes were dispersed in 200 mL of chloroform, and 5 g of photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) was added under the protection of nitrogen and protected from light. 5 g of triethylamine was added dropwise at 25°C and reacted for 3 hours. The reaction mixture was filtered to obtain a black filter cake, which was washed with chloroform to remove excess 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) and triethylamine. After vacuum drying at 25°C in the dark, 10.29 g of carbon nanotubes grafted with the photoinitiator were obtained.
[0175] Weigh respectively: 25g of methyl methacrylate, 25g of hydroxypropyl acrylate, 2g of polyurethane acrylate prepolymer (functionality: 2-4), 20g of conductive carbon black SP, 30g of conductive graphite KS-6, 1g of carboxymethyl cellulose, 1g of BYK-ET3003 wetting and dispersing agent, and 0.5g of para-benzoquinone (inhibitor). The materials are first mechanically stirred at a stirring speed of 500 rpm for 1 hour at room temperature, and then transferred to a sand mill for wet ball milling with zirconium beads having a diameter of 0.8mm, the temperature is controlled at 10°C, and the ball milling time is 4 hours to obtain a pre-dispersed first mixed slurry; under light-proof conditions, 1g of carbon nanotubes grafted with a photoinitiator is added, and first mechanically stirred at a stirring speed of 500 rpm for 1 hour at room temperature, and then transferred to a sand mill for wet ball milling with zirconium beads having a diameter of 0.8mm, the temperature is controlled at 10°C, and the ball milling time is 30 minutes to obtain a slurry for photocuring film formation.
[0176] The 15 μm thick aluminum foil is cleaned with ultrasonic equipment, and then the surface of the aluminum foil is etched with hydrochloric acid solution to increase the roughness of the aluminum foil. The pH value of the hydrochloric acid solution is between 5-7, and the thickness of the corrosion layer does not exceed 5 μm. The acid is washed off after the corrosion treatment.
[0177] Under light-proof conditions, the slurry was coated on aluminum foil using a 5 μm wire rod, and the wet film thickness was 5 μm. The aluminum foil coated with the wet film was placed in a nitrogen atmosphere, and irradiated with ultraviolet light with a wavelength of 300-380 nm for 60 seconds to cure the film to obtain a carbon-coated aluminum foil.
[0178] Comparative Example 1
[0179] Weigh the following: 25 g butyl acrylate, 25 g hydroxyethyl acrylate, 2 g polyurethane acrylate prepolymer (functionality: 2-4), 1 g conductive carbon black SP, 50 g conductive graphite KS-6, 1 g carboxymethyl cellulose, 1 g BYK-ET3003 wetting and dispersing agent, 0.5 g p-hydroxyanisole (inhibitor MEHQ), 1 g single-walled carbon nanotube (outer diameter 1-2 nm, length 5-30 μm, specific surface area greater than 300 m 2 / g). The material was mechanically stirred at a stirring speed of 500 rpm and stirred at room temperature for 1 hour, then transferred to a sand mill and wet-milled with zirconium beads with a diameter of 0.8 mm, at a temperature of 10°C and a ball milling time of 4 hours to obtain a pre-dispersed slurry. Under light-proof conditions, 0.5g of photoinitiator 2959 was added, and mechanical stirring was first performed at a stirring speed of 500 rpm and stirred at room temperature for 1 hour, then transferred to a sand mill and wet-milled with zirconium beads with a diameter of 0.8 mm, the temperature was controlled at 10°C, and wet-milled for 30 minutes to obtain a slurry for photocuring film formation, in which the photoinitiator of the slurry was not grafted onto the carbon nanotubes. Under light-proof conditions, the slurry was coated on aluminum foil with a 5μm wire rod, and the wet film thickness was 5μm. The aluminum foil coated with the wet film was placed in a nitrogen atmosphere, and irradiated with ultraviolet light with a wavelength of 300-380nm for 60s to cure the film to obtain a carbon-coated aluminum foil.
[0180] Comparative Example 2
[0181] Weigh the following: 25 g butyl acrylate, 25 g hydroxyethyl acrylate, 2 g polyurethane acrylate prepolymer (functionality: 4-6), 1 g conductive carbon black SP, 50 g conductive graphite KS-6, 1 g carboxymethyl cellulose, 1 g BYK-ET3003 wetting and dispersing agent, 0.5 g p-hydroxyanisole (inhibitor MEHQ), 1 g single-walled carbon nanotube (outer diameter 1-2 nm, length 5-30 μm, specific surface area greater than 300 m 2 / g). The material was mechanically stirred at a speed of 500 rpm and stirred at room temperature for 1 hour, then transferred to a sand mill and wet-milled with zirconium beads with a diameter of 0.8 mm, at a temperature of 10°C and a ball milling time of 4 hours to obtain a pre-dispersed slurry. 0.5g of thermal initiator BPO (benzoyl peroxide) was added, and mechanical stirring was first performed at a speed of 500 rpm and stirred at room temperature for 1 hour, then transferred to a sand mill and wet-milled with zirconium beads with a diameter of 0.8 mm, the temperature was controlled at 10°C, and wet-milled for 30 minutes to obtain a slurry for thermal curing film formation. The slurry was coated on aluminum foil with a 5μm wire rod, and the wet film thickness was 5μm. The aluminum foil coated with the wet film was placed in a nitrogen atmosphere, and a carbon-coated aluminum foil was obtained after curing for 300s in a heating environment at 150°C to form a film.
[0182] Performance Testing
[0183] (1) Hundred-grid peel strength test
[0184] According to the GB-T9286-1998 method, when testing by the 100-grid method, level 0 means no shedding, level 1 means less than 5% shedding, level 2 means greater than 5% and less than 15% shedding, level 3 means greater than 15% and less than 35% shedding, level 4 means greater than 35% and less than 65% shedding, and level 5 means the shedding degree is greater than level 4.
[0185] (2) NMP resistance and water resistance test
[0186] Use a two-way abrasion tester to fully absorb NMP or water and other test solvents into cotton, and wipe back and forth 200 times in 2 seconds. If the carbon coating layer does not leak the base after more than 200 wipes, it is qualified. If the base leaks after less than 200 wipes, record the maximum number of wipes.
[0187] (2) Electrolyte resistance test.
[0188] The carbon-coated aluminum foil is placed in the electrolyte for 120 days. If there is no obvious shedding of the coating and no discoloration of the electrolyte, it is qualified.
[0189] (3) Square resistance test.
[0190] Tested using Kunde Technology KDB-1 block resistance tester.
[0191] (4) Peel strength test using a tensile testing machine.
[0192] Tested using INSTRON tensile testing machine.
[0193] (5) Horizontal lines
[0194] Visual inspection.
[0195] The above performance test results are recorded in Table 1.
[0196] Table 1:
[0197] Test items Example 1 Example 2 Comparative Example 1 Comparative Example 2 100-grid test Level 0 Level 0 Level 1 Level 2 NMP resistant More than 200 times More than 200 times 146 times 98 times Water resistant More than 200 times More than 200 times 162 times 112 times Electrolyte resistance good good generally good Square resistance 2.3 milliohms per square 2.2 milliohms per square 2.4 milliohms per square 5.8 milliohms per square Carbon coating thickness 0.3μm 0.4μm 0.4μm 0.4μm Peel strength N / m 87 91 63 70 Horizontal stripes none none none With horizontal stripes
[0198] As can be seen from Table 1, both Example 1 and Example 2 used carbon nanotubes grafted with photoinitiators, which increased the entanglement of the polymer after polymerization. In Comparative Example 1, the photoinitiator was not grafted onto the carbon nanotubes, and the entanglement of the polymer after curing into a film was not as good as that of Example 1 and Example 2. Since the polymer entanglement caused the coating adhesion to increase, the peel strength, NMP resistance, water resistance, and electrolyte resistance of Example 1 and Example 2 were all better than those of Comparative Example 1.
[0199] In addition, in Comparative Example 2, thermal curing film formation is used, and thermal curing film formation cannot increase the entanglement of the polymer. At the same time, the volume shrinkage of the coating during the thermal curing process easily leads to defects such as wrinkles and horizontal stripes, resulting in a decrease in the adhesion of the coating. However, Example 1, Example 2 and Comparative Example 1 all use photocuring film formation. The volume shrinkage caused by photocuring is perpendicular to the film surface, and there is no thermal effect. There are fewer defects such as horizontal stripes and wrinkles. The peel strength, NMP resistance, water resistance, and electrolyte resistance of Example 1, Example 2 and Comparative Example 1 are all better than those of Comparative Example 2.
[0200] By the attached Figure 1 , Attachment Figure 2 It can be seen that thermal curing uses an external heat source for heating, and the polymerization reaction itself generates heat. After film formation, the coating is thinner and the heat dissipation is faster. Sudden cooling causes coating stress, which can easily cause defects such as horizontal wrinkles. Figure 1 and Figure 2 In comparison, photocuring film formation does not use an external heat source, which is more conducive to avoiding defects such as horizontal lines and wrinkles.
[0201] Production of positive electrode
[0202] Weigh 50g of N-methylpyrrolidone, then weigh 47.5g of lithium iron phosphate, 1.5g of PVDF binder, and 1g of conductive carbon black SP, add them to N-methylpyrrolidone, stir under normal temperature and anhydrous conditions, mix evenly, and prepare a positive electrode slurry with a solid content of 50%. Use a wire rod to evenly coat the slurry on the aluminum foil current collector, with a single-side coating thickness of 70μm. The positive electrode slurry is coated on the carbon-coated aluminum foil of Example 1, the carbon-coated aluminum foil of Example 2, the carbon-coated aluminum foil of Comparative Example 1, the carbon-coated aluminum foil of Comparative Example 2, and the bare aluminum foil without carbon coating, dried and rolled, and the coating surface density is 2g / cm 2 , and obtain the positive electrode.
[0203] Peel strength test of positive electrode:
[0204] The INSTRON tensile tester was used to test the adhesion between the positive electrode slurry and the carbon-coated aluminum foil before and after rolling the positive electrode sheet. The cutting width of the positive electrode sheet was 3 cm.
[0205] Test results of positive electrode:
[0206] Table 2:
[0207] Aluminum foil for positive electrode Example 1 Example 2 Comparative Example 1 Comparative Example 2 Light Aluminum Foil Adhesion force before rolling (N / m) 11.23 12.16 11.98 10.85 9.33 Adhesion after rolling (N / m) 14.37 14.98 12.04 11.87 10.52
[0208] The main components of the positive electrode slurry are lithium iron phosphate and PVDF binder, and its adhesion to aluminum foil is poor. In the embodiments and comparative examples, there is a carbon coating layer between the positive electrode slurry and the aluminum foil. The carbon coating layer has good adhesion to the aluminum foil and the positive electrode slurry, and can enhance the adhesion between the current collector and the positive electrode slurry. Therefore, the adhesion before and after rolling in the embodiments and comparative examples is greater than that of the bare aluminum foil. In the present invention, the photoinitiator is first grafted onto the carboxylated carbon nanotubes, and then the polymerizable monomer is grafted onto the tube wall of the carbon nanotube grafted by the photoinitiator through photoinitiator fragments to obtain a comb-like structure, which is beneficial to the entanglement of the polymer. The carbon nanotubes and the polymer are in a cross-linked state, which is beneficial to enhancing the adhesion of the carbon coating layer. The adhesion before and after rolling in Examples 1 and 2 is greater than that in Comparative Examples 1 and 2.
[0209] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory. Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be construed as limitations on the present invention, and those of ordinary skill in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a carbon-coated aluminum foil, characterized in that: The preparation method comprises the following steps: (1) Pretreatment: reacting carboxylated carbon nanotubes with thionyl chloride to obtain chlorinated carbon nanotubes; grafting a photoinitiator onto the chlorinated carbon nanotubes to obtain photoinitiator-grafted carbon nanotubes; The photoinitiator is selected from one or more of benzoin derivatives, benzyl ketal compounds, α,α-dialkoxyacetophenone compounds, α-hydroxyalkyl phenone compounds, α-aminoalkyl phenone compounds or acylphosphine oxide compounds; The functionalized carboxyl content of the carboxylated carbon nanotubes is greater than 2 wt %; The mass ratio of the carboxylated carbon nanotubes to thionyl chloride is 1:(0.3-3); The mass ratio of the chlorinated carbon nanotubes to the photoinitiator is 1:(0.3-5); (2) preparing slurry: adding polymerizable monomers, prepolymers, conductive agents and polymerization inhibitors to perform a first mixing; adding carbon nanotubes grafted with photoinitiators to perform a second mixing to obtain slurry; The polymerizable monomer is selected from one or more of acrylic monomers, acrylate monomers, styrene monomers or allyl monomers; The prepolymer is selected from one or more of polyether acrylate, epoxy acrylate resin or polyurethane acrylate; The mass ratio of the polymerizable monomer, prepolymer, conductive agent and polymerization inhibitor is 1: (0.01-0.20): (0.4-2.50): (0.01-0.35); The mass ratio of the polymerizable monomer to the carbon nanotubes grafted with the photoinitiator is (0.8-2): (0.01-0.5); (3) Applying slurry: Applying the prepared slurry on the aluminum foil; (4) Curing: Place the aluminum foil coated with the slurry under ultraviolet light to cure into a film.
2. The preparation method according to claim 1, characterized in that: In step (2), the conductive agent is selected from one or more of conductive carbon black SP, conductive graphite KS-6, graphene, carbon fiber or carbon nanotube; The polymerization inhibitor is selected from one or more of p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butylhydroquinone, hydroquinone, methylhydroquinone, p-benzoquinone, vinyl acetate, aniline, diphenylamine, benzidine or p-phenylenediamine.
3. The preparation method according to claim 1, characterized in that: In step (2), the first mixing includes: first mechanical stirring, then sand grinding; the second mixing includes: first mechanical stirring, then sand grinding; In the first mixing and the second mixing, the temperature of the mechanical stirring is room temperature, and the temperature during sand grinding is controlled within the range of -10 to 10°C.
4. The preparation method according to claim 1, characterized in that: Before applying the slurry in step (3), the aluminum foil is pretreated to increase its surface roughness; The pretreatment step includes: using ultrasonic equipment to clean the surface of the aluminum foil, and then corroding the surface of the aluminum foil with acid or etching the surface of the aluminum foil with plasma equipment.
5. The preparation method according to claim 1, characterized in that: In step (3), the slurry is coated in a dark environment or under a yellow light. The coating method is wire rod coating, doctor blade coating or micro-concave roller coating.
6. The preparation method according to claim 1, characterized in that: In step (3), the thickness of the coated wet film is between 5 and 10 μm.
7. The preparation method according to claim 1, characterized in that In step (4), the UV curing time is 30-100 s, the UV light source wavelength range is 300-380 nm, and the UV light energy is 100-1500 mJ / cm 2 .
8. A carbon-coated aluminum foil, characterized in that: The carbon-coated aluminum foil is prepared by the preparation method described in any one of claims 1 to 7.
9. A current collector comprising the carbon-coated aluminum foil according to claim 8.
Citation Information
Patent Citations
Ultraviolet light cured carbon-coated aluminum foil current collector and preparing method thereof
CN106299380A
Ultraviolet curing coating containing modified carbon nanotube
CN109735210A